Microfabricated magnetic structures for future medicine: from sensors to cell actuators. (October 2012) - Vitol, Elina A; Novosad, Valentyn; Rozhkova, Elena A
In this review, we discuss the prospective medical application of magnetic carriers microfabricated by top-down techniques. Physical methods allow the fabrication of a variety of magnetic structures with tightly controlled magnetic properties and geometry, which makes them very attractive for a cost-efficient mass-production in the fast growing field of nanomedicine. Stand-alone fabricated particles along with integrated devices combining lithographically defined magnetic structures and synthesized magnetic tags will be considered. Applications of microfabricated multifunctional magnetic structures for future medicinal purposes range from ultrasensitive in vitro diagnostic bioassays, DNA sequencing and microfluidic cell sorting to magnetomechanical actuation, cargo delivery, contrast enhancement and heating therapy.